Influence of Neuromarketing Brain Dominance on Brand Equity from the Consumer Perspective, a General Study of Generation Z in the City of Sucre, Bolivia (Revista de Investigaciones Universidad del Quindío, 2022)
The objective of the study was to validate a model to measure the cerebral dominance of neuromarketing considering the multidimensional models of brand value from the perspective of the consumer, taking as object of study a segment that belongs to the population cohort called Generation Z. The research was of exploratory type, applied, quantitative, correlational type - descriptive, with non-experimental design. The studied sample consisted of 342 people between 17 and 25 years old who are also university students. The variables of the model that supports the instrument to measure the brain dominance of neuromarketing over brand value obtained a Cronbach's Alpha, brand value VM (0.807), brain neocórtex CNC (0.883), brain limbic CL (0.923) and brain primitive CP (0.931); on the other hand, complementing the validity and reliability of the construct, for all the variables of the model the rho_A values ​​were greater than 0.7, the composite reliability greater than 0.7 and the mean variance extracted (AVE) greater than 0.5 . Through the interpretation of the Path coefficients, it is verified that the proposed hypotheses were accepted, that the limbic brain (0.370) dominates the Brand Value from the consumer's perspective, followed by the neocórtex brain (0.264) and finally the primitive brain (0.207). Concluding with the validation of the proposed instrument.
Keywords: Neuromarketing; Brand Value; Brain Dominance; Generation Z